2012
DOI: 10.1007/978-1-62703-074-8_32
|View full text |Cite
|
Sign up to set email alerts
|

Thermotherapy, Chemotherapy, and Meristem Culture in Banana

Abstract: Bananas that provide a staple food to the millions of people are adversely affected by several viruses such as Banana bunchy Top Virus (BBTV), Banana Streak Virus (BSV), and Cucumber Mosaic Virus (CMV). These viruses are known to have a devastating effect on crop production and constraint to the international exchange and conservation of banana germplasm-a cornerstone for breeding new cultivars. The viruses are particularly problematic in vegetative propagated crops, like bananas, because of their transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…The accessions that have tested positive for a virus will undergo a sanitation process: thermotherapy and chemotherapy are combined with meristem culture to eliminate the infecting virus (Lassois et al 2013). After therapy, the accession is tested again after 3 and 6 months of greenhouse growth and, if negative, can be available for distribution.…”
Section: Virus Indexingmentioning
confidence: 99%
“…The accessions that have tested positive for a virus will undergo a sanitation process: thermotherapy and chemotherapy are combined with meristem culture to eliminate the infecting virus (Lassois et al 2013). After therapy, the accession is tested again after 3 and 6 months of greenhouse growth and, if negative, can be available for distribution.…”
Section: Virus Indexingmentioning
confidence: 99%
“…Other critical points need to be considered; one of the main difficulties with SAM culture of ranunculus is the high mortality caused by endogenous bacterial contamination. Moreover, the excision of a portion of apical meristem small enough to guarantee a healthy plant may lead to a high risk of non‐viability (Lassois et al ., ). In the current study, sterile and viable SAM explants were obtained from 6% of the meristems excised from buds of a virus‐infected Yellow 1 plant.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that ninety percent of the farmers from the Great Lake Region were able to recognise bunchy top symptoms (Niyongere et al ., ). Moreover, the process of initiating the plants in vitro can eradicate the virus (Lassois et al ., ), further reducing the chance of introducing BBTV into collections. CMV was not detected in our study, neither in pre‐indexing nor indexing steps.…”
Section: Discussionmentioning
confidence: 99%